Cascaded Ripple Carry Adder Based SRCSA for Efficient FIR Filter - Mohamed Syed Ali (Institute of Advanced Engineering and Science, 2018)
Filter is one of the key components of all signals processing elements. Both the FIR and IIR filter are used to reduce the unwanted signal in the original signal. Here discussing the FIR filter and design the efficient FIR filter using Dual Ripple Carry Adder (RCA) based SQRT-carry select adder (CSLA). Many components present in the FIR filter, one of the main component is Adder. Adder is used to combine the signal for avoid the noise occurring in the output. Proposed a Dual RCA based SQRT-CSLA for speed up the filtering process. The filter performance can be analyzed by Xilinx simulation environment.